Dynamic capabilities and knowledge management = Koncepcja dynamicznych zdolności i zarządzanie wiedzą - Krzakiewicz, Kazimierz (Zielona Góra: Faculty of Economics and Management Press)
The dynamic capabilities concept was formed and has been developed by integration of evolutionary theory, transaction cost theory, and the organisational learning and tacit knowledge concepts. As a result, it helps to weaken essential dichotomies of the strategic management theory, especially those relating to ?internal and external? factors, a task that is of particular topical interest in today?s environment. The concept has at the centre of its attention the knowledge of the firm on how to manage its resources proactively in order to form new asset combinations and thereby capture economic rent. This knowledge is of particular importance if firms are to compete in the knowledge economy. The dynamic capabilities paradigm opens up perspectives for the all-encompassing analysis of various business strategy aspects, especially those that are crucial in ensuring a firm?s long term success, such as entrepreneurship, change management or knowledge-based competitiveness.
Keywords: dynamiczne zdolności; zarządzanie wiedzą; Zarządzanie strategiczne; przewaga konkurencyjna; dynamic capabilities; knowledge management; Strategic management; competitive advantage